THE NETWORK OF PROTECTED AREAS IN THE MURMANSK PART OF THE GREEN BELT OF FENNOSCANDIA: HISTORY, CURRENT SITUATION AND PROSPECTS - Боровичев, Евгений Александрович; Королева, Наталья Евгеньевна; Поликарпова, Наталья Владимировна; Петров, Виктор Николаевич; Петрова, Ольга Викторовна; Трусова, Марина Григорьевна; Borovichev, Evgeny; Koroleva, Natalia; Polikarpova, Natalia; Petrov, Viktor; Petrova, Olga; Trusova, Marina (Trudy Karelʹskogo nauchnogo t͡s︡entra Rossiĭskoĭ akademii nauk, 2019)
The history of protected areas (PA) in the Murmansk part of the Green Belt of Fennoscandia (GBF) started back in the late 19th century. The progress and properties of the PA network are associated with the history of the neighboring states and evolution of nature conservation ideas. The current PA network in GBF includes two strict nature reserves, two nature parks, three integrated regional nature reserves (zakazniks) and six regional nature monuments. Taken together, they cover 475 911 hectares, i. e. 16.4 % of the total area of GBF in the Murmansk Region. To optimize the protected areas network in this GBF ecological corridor, it is first of all necessary to establish the Vuorjema Federal Zakaznik and lonn-N'yugoajv Regional Zakaznik. The Vuorjema Federal Zakaznik together with the planned Norwegian PA Grense-Jakobselv will constitute an important node of the international environmental protection network. The Ionn-N'yugoajv Regional Zakaznik will complement the PA system together with Finnish Urho Kekkonen National Park and Laplandsky Les Zakaznik. It is also necessary to complete the reorganization of the Kutsa Zakaznik into the nature park with the prospect of organizing the bilateral Kutsa-Oulanka-Paanajärvi park. For the protected area network to function effectively, it is necessary to confer the status of high conservation value forests on the forest ecosystems along the national borders. Recent additions to Russian national forest legislation in regard to waterside protection forests significantly lower their environmental and conservation value.